Two bromodomain proteins functionally interact to recapitulate an essential BRDT-like function in Drosophila spermatocytes - Shuhei Kimura; Benjamin Loppin (Open Biology, 2015)
In mammals, the testis-specific bromodomain and extra terminal (BET) protein BRDT is essential for spermatogenesis. In Drosophila, it was recently reported that the tBRD-1 protein is similarly required for male fertility. Interestingly, however, tBRD-1 has two conserved bromodomains in its N-terminus but it lacks an extra terminal (ET) domain characteristic of BET proteins. Here, using proteomics approaches to search for tBRD-1 interactors, we identified tBRD-2 as a novel testis-specific bromodomain protein. In contrast to tBRD-1, tBRD-2 contains a single bromodomain, but which is associated with an ET domain in its C-terminus. Strikingly, we show that tbrd-2 knock-out males are sterile and display aberrant meiosis in a way highly similar to tbrd-1 mutants. Furthermore, these two factors co-localize and are interdependent in spermatocytes. We propose that Drosophila tBRD-1 and tBRD-2 associate into a functional BET complex in spermatocytes, which recapitulates the activity of the single mammalian BRDT-like protein.